'Private jurisprudence' and the right to be forgotten balancing test. Issue 39 (November 2020) - Leiser, M.R.
Abstract: Upon receipt of a right to be forgotten request, private actors like Google are responsible for implementing the balancing test between competing rights of privacy and data protection and free expression and access to information. This amounts to private jurisprudence that data subjects, lawyers, and interested parties could, theoretically, game to their advantage. This paper critiques this process and argues two separate, but related points. (1) Search engines have become the sole arbiter of the rights to privacy and data protection under Articles 7 and of the Charter of Fundamental Rights and Articles 8 and 10 of the European Convention of Human Rights, when safeguarding should be a responsibility of state authorities. (2) As private actors face litigation if their decision is not acceptable to the data subject, the right to access information and the public's right to know is compromised. Search engines exert considerable power over access to and Internet usage, yet nevertheless benefit from frameworks that permit a lack of adherence to similar human rights standards as public actors or agencies. As such, empowering search engines as decision-makers over conflicting fundamental rights is problematic. Rather than allow the content of the right to be forgotten to be fleshed out by private actors, the significant body of existing jurisprudence should form the basis for public guidelines on how to implement the right to be forgotten. An analysis of case law of national courts, the European Court of Human Rights and the CJEU reveals two related matters: it is possible to reverse engineer how search engines determine which requests will be actioned and those which will be denied. This paper argues a) collectively the body of jurisprudence is of sufficient standing to develop a public and transparent balancing test that is fair to all stakeholders and b) private actors should no longer be resolving the conflict between competing fundamental rights. The paper closes by positing a framework, loosely based on ICANN's Uniform Domain Resolution Procedure for resolving conflict between conflicting cyber property rights that provides transparency and accountability to the right to be forgotten and removes search engines as arbiters of the balancing test in select cases.